PENGARUH KOMPETENSI KEWIRAUSAHAAN DAN EKSPEKTASI PENGHASILAN TERHADAP NIAT MENJADI WIRAUSAHA DI KALANGAN MAHASISWA JURUSAN MANAJEMEN PERHOTELAN POLITEKNIK MANDIRI BINA PRESTASI MEDAN - Yulvitriyani br Sebayang; Vera Kristina Hutagalung (Smart Education, 2026)
Abstract: This study aims to examine the influence of entrepreneurial competencies and income expectations on the intention to become an entrepreneur among students in the Hospitality Program at Politeknik Mandiri Bina Prestasi Medan. The background of this study is based on the high unemployment rate among higher education graduates and the low level of interest in entrepreneurship among college graduates. The research method used is quantitative, with a des by a significance value of less than 0.05. This means that the higher the students’ entrepreneurial competence, the stronger their intention to start a business.criptive and associative approach. The research population consists of all students in the Hospitality Study Program at the Mandiri Bina Prestasi Polytechnic in Medan, totaling 258 people. The sample was selected using the Slovin formula with a 5% margin of error, resulting in 157 respondents. Data collection was conducted via a questionnaire that had been tested for validity and reliability. Data analysis was performed using multiple linear regression with SPSS software. The findings indicate: (1) Entrepreneurial competence has a positive and significant influence on the intention to become an entrepreneur, as evidenced. (2) Income expectations also have a positive and significant influence on the intention to become an entrepreneur, as evidenced by a p-value of less than 0.05. This indicates that the higher students’ expectations regarding income from entrepreneurship, the stronger their intention to pursue it. (3) Together, entrepreneurial competence and income expectations have a positive and significant influence on the intention to become an entrepreneur, as indicated by an F-statistic value greater than the critical F-value (3.06) and a significance level of less than 0.05. The coefficient of determination (R²) value of 0.585 indicates that 58.5% of the variation in entrepreneurial intention can be explained by these two independent variables. The remaining 41.5% is associated with other variables not considered in this study, such as family environment, self-confidence, motivation, and financial literacy. Respondent characteristics show that the majority of students have taken entrepreneurship courses (70.1%), have not yet started a business (71.3%), and are inspired by their families (36.9%). Among those who have started or are currently running a business, the majority are in the culinary sector (48.9%), which is relevant to their hospitality education background. This study supports Ajzen’s Theory of Planned Behavior and Vroom’s Expectancy Theory. Recommendations for the Mandiri Bina Prestasi Polytechnic in Medan include strengthening the entrepreneurship curriculum with practice-based learning, organizing entrepreneurship development programs, and providing support to students who wish to start their own businesses. Future researchers are advised to include additional variables and expand the scope of their research. Keywords: Entrepreneurial Competence, Income Expectations, Entrepreneurial Intentions, Hospitality Students. Abstrak: Penelitian ini bertujuan untuk mengkaji pengaruh kompetensi kewirausahaan dan ekspektasi pendapatan terhadap niat menjadi wirausaha di kalangan mahasiswa Program Studi Perhotelan Politeknik Mandiri Bina Prestasi Medan. Latar belakang penelitian ini didasarkan pada tingginya tingkat pengangguran di kalangan lulusan pendidikan tinggi dan rendahnya minat kewirausahaan di kalangan lulusan perguruan tinggi. Metode penelitian yang digunakan adalah kuantitatif, dengan pendekatan deskriptif dan asosiatif. Populasi penelitian terdiri dari seluruh mahasiswa Program Studi Perhotelan di Politeknik Mandiri Bina Prestasi Medan, sebanyak 258 orang. Sampel dipilih menggunakan rumus Slovin dengan margin of error 5%, sehingga diperoleh 157 responden. Pengumpulan data dilakukan melalui kuesioner yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan menggunakan regresi linier berganda dengan program SPSS. Temuan menunjukkan: (1) Kompetensi kewirausahaan memiliki pengaruh positif dan signifikan terhadap niat untuk menjadi wirausaha, sebagaimana dibuktikan dengan nilai signifikansi kurang dari 0,05. Hal ini berarti bahwa semakin tinggi kompetensi kewirausahaan mahasiswa, semakin kuat pula niat mereka untuk memulai usaha. (2) Ekspektasi pendapatan juga memiliki pengaruh positif dan signifikan terhadap niat untuk menjadi wirausaha, yang didukung oleh nilai signifikansi kurang dari 0,05. Hal ini menunjukkan bahwa semakin tinggi ekspektasi mahasiswa terkait pendapatan dari kewirausahaan, semakin kuat pula niat mereka untuk menekuninya. (3) Secara bersama-sama, kompetensi kewirausahaan dan ekspektasi pendapatan memiliki pengaruh positif dan signifikan terhadap niat untuk menjadi wirausaha, sebagaimana ditunjukkan oleh nilai statistik F yang lebih besar dari nilai tabel F (3,06) dan nilai signifikansi kurang dari 0,05. Nilai koefisien determinasi (R²) sebesar 0,585 menunjukkan bahwa 58,5% variasi dalam niat kewirausahaan dapat dijelaskan oleh kedua variabel independen ini. Sisa 41,5% dikaitkan dengan variabel lain yang tidak dipertimbangkan dalam studi ini, seperti lingkungan keluarga, kepercayaan diri, motivasi, dan literasi keuangan. Karakteristik responden menunjukkan bahwa sebagian besar mahasiswa telah mengikuti mata kuliah kewirausahaan (70,1%), belum memulai usaha (71,3%), dan terinspirasi oleh keluarga mereka (36,9%). Di antara mereka yang telah memulai atau sedang menjalankan usaha, mayoritas berada di sektor kuliner (48,9%), yang relevan dengan latar belakang pendidikan perhotelan mereka. Penelitian ini mendukung Teori Perilaku Terencana (Ajzen) dan Teori Ekspektasi (Vroom). Rekomendasi untuk Politeknik Mandiri Bina Prestasi Medan meliputi penguatan kurikulum kewirausahaan dengan pembelajaran berbasis praktik, penyelenggaraan program pengembangan kewirausahaan, serta pemberian dukungan kepada mahasiswa yang ingin memulai usaha sendiri. Para peneliti di masa mendatang disarankan untuk memasukkan variabel tambahan dan memperluas cakupan penelitian. Kata kunci: Kompetensi Kewirausahaan, Ekspektasi Penghasilan, Niat Berwirausaha, Mahasiswa Jurusan Perhotelan